2017
DOI: 10.1039/c7ib00020k
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin and ICAM-1 synergy in mediating THP-1 monocyte adhesion in hemodynamic flow is length dependent

Abstract: The tightly orchestrated recruitment of monocytes, whose progeny are critical to the progression and resolution of various physiological and pathophysiological processes, is implicated in the time course, severity, and resolution of pathology. Using a microfluidic-based cell adhesion assay integrating spatiotemporal analyses and micropatterning of adhesive proteins, we interrogated the effects of adhesive molecule presentation length, which varies in vivo with disease and stage, on THP-1 monocyte cell rolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…Our results revealed a striking similarity in the relationships of mean percent binding time of LS174T and Colo205 metastatic cells on P-selectin with instantaneous velocity, rolling percentages, and selectin concentration sensitivity with these same relationships for L-selectin-mediated adhesion (Figures 6A–6H and 7G–7HG ). Since L-selectin is primarily responsible for tethering and secondary cell capture of leukocytes at later time points in the cell recruitment processes [ 15 , 65 , 66 ] and can mediate adhesion with leukocytes in free flow [ 67 ], the similarity of metastatic cell adhesion persistence facilitated by P-selectin to that of L-selectin may suggest that P-selectin has a higher potential to functionally facilitate heterotypic aggregation of metastatic cells with activated platelets via platelet expressed P-selectin rather than mediating direct, sustained rolling adhesion on the inflamed endothelium. Indeed, McCarty et al reported that metastatic LS174T and Colo205 cells initially tether to P-selectin expressed by surface-immobilized platelets in a manner that is stabilized by engagement of von Willebrand factor [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed a striking similarity in the relationships of mean percent binding time of LS174T and Colo205 metastatic cells on P-selectin with instantaneous velocity, rolling percentages, and selectin concentration sensitivity with these same relationships for L-selectin-mediated adhesion (Figures 6A–6H and 7G–7HG ). Since L-selectin is primarily responsible for tethering and secondary cell capture of leukocytes at later time points in the cell recruitment processes [ 15 , 65 , 66 ] and can mediate adhesion with leukocytes in free flow [ 67 ], the similarity of metastatic cell adhesion persistence facilitated by P-selectin to that of L-selectin may suggest that P-selectin has a higher potential to functionally facilitate heterotypic aggregation of metastatic cells with activated platelets via platelet expressed P-selectin rather than mediating direct, sustained rolling adhesion on the inflamed endothelium. Indeed, McCarty et al reported that metastatic LS174T and Colo205 cells initially tether to P-selectin expressed by surface-immobilized platelets in a manner that is stabilized by engagement of von Willebrand factor [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of vascular injury, monocyte and platelet accumulation and aggregation at denuded vascular regions also rely on adhesive interactions with P-selectin [ 12 ]. While L-selectin expressed on leukocytes can interact with corresponding ligands on the endothelium of high-endothelial venules or the inflamed endothelium of non-lymphoid tissues [ 13 , 14 ], when expressed by leukocytes adherent to the endothelium, it can additionally facilitate secondary capture of circulating cells [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of cells were categorized as photoconverted positive (PC+), with the remaining in the photoconverted negative (PCÀ) population (gates defined based on the non-photoconverted cell population) when perfused over P-selectin functionalized surfaces at 0.5 dyn/cm 2 under exposure to 405 nm light, restricted to a length of 10 mm in the direction of flow (Figure 4F). These frequencies were altered by both adjustments to the laser power, flow rate (e.g., wall shear stress), as well as selectin type (P-, E-, versus L-), the latter mediating rolling adhesion at velocities that vary by orders of magnitude (Edwards et al, 2017;Napier et al, 2007;Oh et al, 2015;Thomas et al, 2008) (Table S3), indicating the sensitivity of this methodology to the kinetic process studied. A PC+ cell population isolated by perfusion through a P-selectin functionalized microchannel at 0.5 dyn/cm 2 under exposure to 405 nm light and sorting via FACS exhibited enhanced extents of rolling adhesion upon reperfusion under identical conditions (P-selectin functionalized substrate, 0.5 dyn/cm 2 wall shear stress) compared to both PCÀ and unsorted cell populations (though not to a statistically significant extent as this comparison lacked power at n = 6) ( Figure 4G).…”
Section: Photoconversion Residence Time and Velocity Probe Differentimentioning
confidence: 99%
“…Metastasis, which is the leading cause of mortality among patients with colon cancer (Massagué and Obenauf, 2016;Welch and Donaldson, 1979), comprises a highly complex sequence of time-and length-scale-regulated steps (Edwards and Thomas, 2017;Lote et al, 2017) that ultimately enable cancer cells to disseminate through the circulation and eventually form secondary tumors (Figure 1Ai). Hemodynamic force hence facilitates the transport of blood-borne metastatic cancer cells to distant organs (Figure 1Aii) but, in order to slow cells down for eventual arrest and extravasation, also stipulates that adhesion underpin the process of extravasation ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation